1998
DOI: 10.1097/00005768-199801000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of creatine supplementation on body composition, strength, and sprint performance

Abstract: The addition of creatine to the glucose/taurine/electrolyte supplement promoted greater gains in fat/bone-free mass, isotonic lifting volume, and sprint performance during intense resistance/agility training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
260
4
11

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(289 citation statements)
references
References 39 publications
14
260
4
11
Order By: Relevance
“…The imposing of work loads using the protocol of 80% of 1MDVMA, as demonstrated in this investigation, allowed to observe that regardless the nutritional supplementation used as ergogenic resource, these positive alterations occur more significantly. Nevertheless, the results of this study corroborate with others (16,(23)(24)(25)(26)(27)(28) , where positive alterations were found in the anthropometric variables (BMI, BM) and in the increase of the MDSR, confirming the theory that the CrH 2 O supplementation can promote positive physiological and biochemical alterations in the organism, causing morphological benefits and consequently promoting improvement in physical and sportive performance. Recent evidence demonstrated by Haussinger and Lang (29) and Haussinger et al (30) show that the increase of the cellular volume is modulated by amino acids and hormones which regulate the activities of the transporter ions and the ionic channels present in the plasmatic membrane, affecting the potential of the membrane or regulating the substrates that are transported by dependence of Na + .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The imposing of work loads using the protocol of 80% of 1MDVMA, as demonstrated in this investigation, allowed to observe that regardless the nutritional supplementation used as ergogenic resource, these positive alterations occur more significantly. Nevertheless, the results of this study corroborate with others (16,(23)(24)(25)(26)(27)(28) , where positive alterations were found in the anthropometric variables (BMI, BM) and in the increase of the MDSR, confirming the theory that the CrH 2 O supplementation can promote positive physiological and biochemical alterations in the organism, causing morphological benefits and consequently promoting improvement in physical and sportive performance. Recent evidence demonstrated by Haussinger and Lang (29) and Haussinger et al (30) show that the increase of the cellular volume is modulated by amino acids and hormones which regulate the activities of the transporter ions and the ionic channels present in the plasmatic membrane, affecting the potential of the membrane or regulating the substrates that are transported by dependence of Na + .…”
Section: Discussionsupporting
confidence: 91%
“…This idea is supported by the fact that the anabolic effects are able to be quantitatively minimized by cells hydrated in hypoosmotic medium. According to Kreider (24) ; Ziegenfuss et al (31) ; Vandenberghe et al (32) ; Haussinger et al (30) ; Bessman and Savabi (33) this alteration may be interpreted as one of the factors responsible for the increase of proteins synthesis (anabolism) or by the reduction of the protein degradation (catabolism), or when these mechanisms are observed associated with creatine supplementation. Corroborating this theory, Ingwall (34) has reported that the creatine addition to incubated skeletal muscular cells increases the in vitro myosin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be effective in enhancing strength and power performance and increasing lean body mass (25,31,33). Most studies examining creatine supplementation generally employed a week-long loading phase (20 gÁd 21 ) followed by daily maintenance doses (5 gÁd 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, the American College of Sports Medicine estimated that 2,500 metric tons were consumed every year (Terjung et al 2000). Creatine improves sport performance during repeated short-duration/high-intensity exercises (Balsom et al 1995) and amplifies the increase in lean body mass and strength induced by resistance training (Kreider et al 1998). Creatine has also therapeutic benefits, it accelerates skeletal muscle recovery after prolonged immobilization (Hespel et al 2001) and it slows down muscle wasting in certain myopathies (Louis et al 2003;Tarnopolsky et al 2004).…”
Section: Introductionmentioning
confidence: 99%